I see Uncle Ben Greene, Charlie Walsh (playing the accordion), Monica Walsh and Uncle Dennis Ryan. Don't know who the other two are. This is in the kitchen in the house in Jerseyside (1950)
Individuals photographed, if any, have been identified within the title from left to right.